2015
DOI: 10.1111/cen.12846
|View full text |Cite
|
Sign up to set email alerts
|

Low iodine diet in differentiated thyroid cancer: a review

Abstract: SummaryRadioactive iodine (RAI) ablation is a beneficial, adjuvant therapy for the management of differentiated thyroid cancer (DTC) after thyroidectomy. The goal of RAI is to destroy remnant thyroid and microscopic cancerous tissue. Radioactive iodine uptake is enhanced by elevating TSH levels and initiating a low iodine diet (LID) prior to ablation. An ideal LID should preferably not exceed 50 mcg/day of dietary iodine for 1-2 weeks, although the duration may be shortened to a week with a structured patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 59 publications
0
52
0
7
Order By: Relevance
“…Studies examining diet and thyroid cancer outcome are scarce. Post-thyroidectomy thyroid cancer patients are often placed on low-iodine diets before radioactive iodine (RAI) treatment in order to enhance I-131 uptake and maximize the destruction of cancerous thyroid cells 13 . One study found that among a cohort of Korean females, approximately 37% did not know that fish pastes, hams, and sausages contained high levels of iodine, and 36% over-estimated the amount of dairy they were allowed to consume on a low-iodine diet 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining diet and thyroid cancer outcome are scarce. Post-thyroidectomy thyroid cancer patients are often placed on low-iodine diets before radioactive iodine (RAI) treatment in order to enhance I-131 uptake and maximize the destruction of cancerous thyroid cells 13 . One study found that among a cohort of Korean females, approximately 37% did not know that fish pastes, hams, and sausages contained high levels of iodine, and 36% over-estimated the amount of dairy they were allowed to consume on a low-iodine diet 14 .…”
Section: Discussionmentioning
confidence: 99%
“…A second limitation is the low-iodine diet which patients had to adhere to in order to increase the effectiveness of RAI treatment. Although this diet is different from a “low-sodium” diet, any foods containing iodized salt and sea salt were not allowed [19]. Therefore, we cannot exclude that this diet might have influenced the sodium and chloride levels and hence osmolality in our patients during hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of iodine restriction is to increase the expression of the sodium‐iodide symporter (NIS) in the thyroid follicular cells by lowering the iodine concentration within the body. It also minimizes the competitive handling of nonradioactive iodine instead of the radioactive iodine by the NIS …”
Section: Introductionmentioning
confidence: 99%